KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN TEORI NEWMAN’S ERROR - Muhaimin, Ulum Rosyidah; Masamah, Ulfa (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN TEORI NEWMAN’S ERROR Ulum Rosyidah Muhaimin1, Ulfa Masamah2 Tadris Matematika, FITK, UIN Maulana Malik Ibrahim Malang ulumrosyidah1@gmail.com, ulfamasamah@uin-malang.ac.id ABSTRACT This research aims to analyze junior high school students' errors in solving System of Linear Equations in Two Variables (SPLDV) story problems using Newman's Error Analysis (NEA). Errors in understanding, transformation, process skills, and drawing conclusions are errors that are analyzed. Six class IX-A students at MTs Modern Al-Rifa'ie Gondanglegi took part in this qualitative research using case study research. Tests and semi-structured interviews were used to collect data and the Miles and Huberman model was used for analysis. Research shows that high-ability students often make mistakes related to transformation and process skills. Although low-ability students made errors in almost every category, moderate-ability students also made coding errors. These findings emphasize the need for intensive guidance in understanding, transforming and resolving SPLDV story problems.